Sistem Pemeriksa Pola Kalimat Bahasa Indonesia berbasis Algoritme Left-Corner Parsing dengan Stemming - Hartanto Kusuma Wardana; Iswara Swanita; Banu Wirawan Yohanes (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
In recent years, human computer interaction has been attracted many researchers and applied in various applications. In order to understand human language, the computer is required to learn human language grammar, one of the languages is Bahasa Indonesia. Left-corner parsing algorithm is used extensively to check English grammar. However, only several implementations are found in Bahasa Indonesia. By combining Left-Corner Parsing algorithm with stemming algorithm, to reproduce basic word and word type before the sentence is parsed according to production rules defined, this article discusses Bahasa Indonesia sentence pattern checking system testing for four single sentence patterns, i.e., Subject-Predicate, SP-Object, SP-Adverb, and SPOA. The testing resultshows the accuracy of sentence pattern recognition of 95.3%.